Chinese participation in Philippine culture and economy - Liao, Shubert S. C. , ed ([Philippines, 1964)
'The greater portion of this book are ... articles written by ... economists, industrialists, professionals, and scholars.'
Keywords: Chinese in foreign countries; Phil. - -- Foreign populations. I. Title